Nanotechnology : an overview - Fonash, Stephen J.
This program explains, "What Is Nanotechnology", and why is it being called "The Machine Shop Technology of the 21st Century"? This presentation is a description of what the popular press calls nanotechnology and presents an overview of what it is and what it is not. Both top-down and bottom-up nanotechnology is described.